2019
DOI: 10.1371/journal.pone.0210189
|View full text |Cite
|
Sign up to set email alerts
|

Faculty perceptions and knowledge of career development of trainees in biomedical science: What do we (think we) know?

Abstract: The Broadening Experiences in Scientific Training (BEST) program is an NIH-funded effort testing the impact of career development interventions (e.g. internships, workshops, classes) on biomedical trainees (graduate students and postdoctoral fellows). BEST Programs seek to increase trainees’ knowledge, skills and confidence to explore and pursue expanded career options, as well as to increase training in new skills that enable multiple career pathways. Faculty mentors are vital to a trainee’s professional deve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
36
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
3
1

Relationship

3
6

Authors

Journals

citations
Cited by 27 publications
(37 citation statements)
references
References 10 publications
1
36
0
Order By: Relevance
“…For example, Midwest-BEST is a regional alliance of several sites in the Midwest (WSU, University of Chicago, and MSU), UCSF, and UC Davis are collaborating on their internship program, 29 and MSU and Vanderbilt have collaborated with NYU, UR, UNC, and UC Denver on a faculty survey to analyze changes in perception of their approaches. 9 Sites report that new career services offices have formed, and their "BEST" offices obtained financial support from their institutions. Some programs received alumni funds, some have been integrated into existing offices of career development, and others are receiving funds from industry partners.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, Midwest-BEST is a regional alliance of several sites in the Midwest (WSU, University of Chicago, and MSU), UCSF, and UC Davis are collaborating on their internship program, 29 and MSU and Vanderbilt have collaborated with NYU, UR, UNC, and UC Denver on a faculty survey to analyze changes in perception of their approaches. 9 Sites report that new career services offices have formed, and their "BEST" offices obtained financial support from their institutions. Some programs received alumni funds, some have been integrated into existing offices of career development, and others are receiving funds from industry partners.…”
Section: Discussionmentioning
confidence: 99%
“…We present some initial descriptive data on trainees’ confidence, development of infrastructure and sustainability, and association of BEST activities with TTD. The influence of BEST programs on faculty attitudes has been addressed by the awardees . Although it is premature to draw meaningful conclusions about the long‐term outcomes of the BEST programs, the baseline information presented here provides insights into program activities and the attitudes and expectations of trainees and faculty.…”
Section: Introductionmentioning
confidence: 99%
“…Studies published by BEST institutions have further reinforced this change in faculty attitudes (25). These studies showed that faculty's initial hesitation is evolving to an understanding that next-generation scientists will not only need to be excellent researchers, but also need to be equipped with professional skills that are more effectively learned outside the laboratory.…”
Section: Culture Changementioning
confidence: 99%
“…While the majority of faculty may not have the resources or experience to support their trainee's career interests, they may impact psychosocial support that is important for trainee confidence in pursuing broad careers. Faculty perspectives on this, for example Watts et al (2019), vary and there are faculty who overtly are not supportive of their trainees pursuing broad career outcomes due to a lack of knowledge about non-academic career options (Dowd & Kaplan, 2005) or are pressured to develop protégés that are well placed in academia (Blackburn, Chapman, & Cameron, 1981;Fogarty & Saftner, 1993;Watts et al, 2019). From a trainee perspective, this lack of support can pose challenges to development for broader career outcomes (Chatterjee et al, 2019).…”
Section: The Role Of Facultymentioning
confidence: 99%